Debunking Misinformation and Communicating Critical Events in Vaccine Trials - Paula Memenga; Sarah Eitze; Parichehr Shamsrizi; Marylyn M. Addo; Cornelia Betsch (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Misinformation and media reports about critical events in vaccine trials challenge public confidence in Covid-19 vaccine safety. Three online experiments using 2×2 between-subjects designs examined the impact of vaccine type, misinformation debunking, and critical events during vaccine trials. In Experiment 1, N = 984 participants received information about different vaccines and misinformation was debunked. In Experiment 2, N = 1,018 participants were informed about different vaccines and trial discontinuation. In Experiment 3, N = 1,006 participants received information about discontinuation and questionable research practices of a manufacturer. The main dependent variables were confidence in vaccine safety, vaccination intention, and willingness to participate in a vaccine trial. Debunking increased vaccination intention and confidence (both η2p = .01) which was partly higher for classical than for new vaccines (η2p  = .01). Information about discontinuation had no effect, but having heard about it before had benefits. Information about questionable research practices decreased confidence ( η2p = .01) and vaccination intention ( η2p = .02) regarding the target vaccine but did not affect other vaccines. Confidence (β = .47) was most strongly associated with willingness to participate in vaccine trials. Critical events in vaccine trials should be communicated transparently to increase confidence, trial participation, and vaccination intentions.